Does B7-H4 expression correlate with clinicopathologic characteristics and survival in ovarian cancer?: A systematic review and PRISMA-compliant meta-analysis. Issue 32 (August 2018) - Ye, Yun; Wang, Jian-Jun; Li, Su-Liang; Wang, Sheng-Yu; Jing, Fa-Hong
Abstract: Background: Several studies have shown that B7-H4 expression is significantly increased in ovarian cancer. However, the role of B7-H4 expression in ovarian cancer remains unclear, and some studies reporting conflicting results. A systematic review of the literature and meta-analysis were conducted to assess the clinicopathologic characteristics and prognostic significance of B7-H4 in ovarian cancer. Methods: Eligible studies were searched in the PubMed, MEDLINE, Cochrane Library, and the China National Knowledge Infrastructure databases. The included studies assessed the relationship between B7-H4 expression and clinicopathologic features or prognosis in patients with ovarian cancer through September 2017. A total of 1045 patients in 10 studies were included in the meta-analysis. Stata software version 12.0 was used to analyze the data. We used an odds ratio (OR) or hazard ratio (HR) with a 95% confidence interval (CI) to assess the risk or hazard association. Results: B7-H4 expression in ovarian cancer patients was significantly increased (OR: 4.20, 95% CI: 2.85–6.18, Z = 6.91, P < .05), and heterogeneity was low between studies ( I 2 = 8.2%, P = .366). With respect to the clinicopathologic features, no relation was detected between B7-H4 expression and International Federation of Gynaecology and Obstetricsstages stages (OR: 0.81, 95% CI: 0.64–1.03, Z = 1.70, P = .09), pathologic grade (OR: 0.91, 95% CI: 0.72–1.16, Z = 0.76, P = .45), tumor metastasis (OR: 1.25, 95% CI: 0.90–1.74, Z = 1.34, P = .18), or histologic type (OR: 1.17, 95% CI: 0.85–1.60, Z = 0.96, P = .34) in ovarian cancer. Furthermore, B7-H4 expression was significantly associated with a worse progression-free survival (PFS) (HR: 1.30, 95% CI: 1.17–1.45, Z = 4.79, P < .05). Conclusion: B7-H4 expression was related to ovarian cancer, but not to patients' clinicopathologic characteristics. High B7-H4 expression was negatively correlated with survival outcome, suggesting that B7-H4 plays an essential role in poor prognosis in ovarian cancer patients.